Proteomic allergen-peptide/protein interaction assay for the identification of human skin sensitizers - Dietz, Lisa; Kinzebach, Sven; Ohnesorge, Stefanie; Franke, Bastian; Goette, Irina; Koenig-Gressel, Dieter; Thierse, Hermann-Josef (Toxicology in vitro, 2013)
Modification of proteins by skin sensitizers is a pivotal step in T cell mediated allergic contact dermatitis (ACD). In this process small reactive chemicals interact covalently or non-covalently with cellular or extracellular skin self-proteins or self-peptides to become recognized by the human immune system. Aiming to develop a novel non-animal in vitro test system for predicting sensitization potential of small reactive chemicals in human skin the allergen-peptide/protein interaction assay (APIA) has been developed. By applying modern proteomic technologies together with a target peptide containing all amino acids, the assay permits the profiling of all amino acid specific allergen-peptide interactions. Moreover, potentially crucial allergen-specific Cys-modifications are qualitatively monitored by mass spectrometry and confirmed by a dual peptide approach. Assay conditions chosen mimic the distinct human epidermal reactivity compartments of the skin surface (pH 5.5), stratum basale (pH 6.8), and typical physiological conditions (pH 7.4). An extreme as well as a moderate human contact sensitizer produced Cys-specific mass shifts, whereas a skin irritant did not. Our data indicate that MALDI-MS based and skin-related in vitro technology platforms - like the APIA - are promising tools in developing alternative non-animal allergen assays. This will assist in chemical classification and next generation risk assessment strategies, including REACH and experimental immunotoxicology.
Available online 17 August 2012